GAMBARAN PERKEMBANGAN PERILAKU EMOSIONAL ANAK : DESCRIPTION OF THE DEVELOPMENT OF CHILDREN'S EMOTIONAL BEHAVIOR - Puspa Kusumaningsih, Tri; Safitri, Ririn (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
ABSTRACT The golden period of child development occurs at the age of the first five years of the child. The development of children's emotional behavior is a slow process. Achievement of this process until the child finds self-controlling behavior and feels comfortable. Based on a preliminary study at ABA 2 Pangen Rejo Kindergarten, Purworejo, out of 104 toddlers, 5 of them lead to emotional disorders. The purpose of this study was to describe the development of children's emotional behavior in Kindergarten ABA 2 Pangenrejo Purworejo. This research research method uses descriptive research methods, population 104 and sample 50. purposive sampling technique. April 2021 research time. Data collection uses a checklist. The data processing technique used percentage techniques with SPSS 17. The results of the study were based on univariate analysis, the majority of children developing normal emotional behavior. The normal category is 80%, and the abnormal category is 20%. The conclusion of the research is that the emotional behavior of children in Kindergarten ABA 2 is normal. It is hoped that parents, caregivers and teachers can work together with health workers to carry out early detection of child development, so that the development of children's emotional behavior can be properly directed. Keywords: Development of Children's Emotional Behavior